Alternate Endpoints for Phase II Trials in Advanced Neuroendocrine Tumors. (2nd August 2018) - Imaoka, Hiroshi; Sasaki, Mitsuhito; Takahashi, Hideaki; Hashimoto, Yusuke; Ohno, Izumi; Mitsunaga, Shuichi; Watanabe, Kazuo; Umemoto, Kumiko; Kimura, Gen; Suzuki, Yuko; Kan, Motoyasu; Ikeda, Masafumi
Abstract: Background: In phase II trials for neuroendocrine tumors (NETs), the objective response rate (ORR) is traditionally used as a primary endpoint. However, the validity of the ORR as a primary endpoint has never been systematically examined. Therefore, a literature‐based analysis of phase II trials for NETs was performed to identify valid alternative endpoints for predicting median progression‐free survival (PFS) in clinical trials for NETs. Materials and Methods: Phase II trials of medical treatment for advanced NETs were identified based on a systematic search using MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials. Results: A total of 22 trials were identified, and 1, 310 patients and 27 treatment arms were included in the analysis. There was no significant relationship between the ORR and median PFS ( r = .374; 95% confidence interval [CI], −0.051 to 0.800; p = .085). Conversely, 12‐month PFS rates showed very strong correlations with median PFS ( r = .929; 95% CI, 0.831–1.027; p < .001). Conclusion: The results of the present analysis indicate that the ORR is not significantly correlated with median PFS and suggest that 12‐month PFS rates are good alternate endpoints for screening phase II trials for NETs. Implications for Practice: Phase II trials are screening trials that seek to identify agents with sufficient activity to continue development. Thus, earlier endpoints are preferable, and the objective response rate (ORR) has been traditionally used as a surrogate endpoint in phase II trials for neuroendocrine tumors (NETs). However, the present study showed that the ORR was not significantly correlated with median progression‐free survival (PFS). On the other hand, the 12‐month PFS rate showed very strong correlation with median PFS and is considered a good alternate endpoint for screening phase II trials for NETs. Abstract : A literature‐based study of prospective trials of neuroendocrine tumor (NET) treatments was performed to identify valid alternative endpoints for predicting median progression‐free survival (PFS) in clinical trials.